Relación del polimorfismo phe31ile y niveles de expresión del gen stk15 en cáncer de mama femenino - Oña Cisneros, Fabián David (2014)
The STK15 gene, which encodes for the Aurora-A protein, has attracted attention due its´ direct relationship with cell cycle by acting both centrosome maturation and proper spindle assembly in cell mitosis. The Phe31Ile (1712T A) polymorphism of STK15 gene has been identified as an altering functional kinase, Ile31 variant is associated with the occurrence of erroneous chromosomal segregation and tumor progression. The aim of this study was to associate Phe31Ile polymorphism and the expression of STK15 gene with the risk of developing breast cancer and establish relationships with hormonal factors, tumor characteristics and stage of disease in Ecuadorian mestizo female population. This case-control study examined the contribution of this polymorphism to susceptibility to the development and progression of breast cancer...